2012
DOI: 10.1073/pnas.1119828109
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of the auditory thalamus in developmental dyslexia

Abstract: Developmental dyslexia, a severe and persistent reading and spelling impairment, is characterized by difficulties in processing speech sounds (i.e., phonemes). Here, we test the hypothesis that these phonological difficulties are associated with a dysfunction of the auditory sensory thalamus, the medial geniculate body (MGB). By using functional MRI, we found that, in dyslexic adults, the MGB responded abnormally when the task required attending to phonemes compared with other speech features. No other structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
154
4
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(179 citation statements)
references
References 61 publications
17
154
4
3
Order By: Relevance
“…Interestingly, a similar pattern of atypical neuronal morphology was also present in the MGN of dyslexics with more small and fewer large neurons [31]. This finding is further supported by recent functional imaging data showing abnormal activity in the region of the MGN in dyslexic individuals during an auditory phoneme discrimination task [34]. Numerous studies also report impaired processing of rapid, but not slow, auditory information in language and reading impaired populations, including SLI and dyslexia, and even at-risk infants [29,[35][36][37][38][39][40][41][42][43].…”
Section: Introductionsupporting
confidence: 68%
“…Interestingly, a similar pattern of atypical neuronal morphology was also present in the MGN of dyslexics with more small and fewer large neurons [31]. This finding is further supported by recent functional imaging data showing abnormal activity in the region of the MGN in dyslexic individuals during an auditory phoneme discrimination task [34]. Numerous studies also report impaired processing of rapid, but not slow, auditory information in language and reading impaired populations, including SLI and dyslexia, and even at-risk infants [29,[35][36][37][38][39][40][41][42][43].…”
Section: Introductionsupporting
confidence: 68%
“…Correspondingly, short-term adaptation of auditory and visual cortices to the statistics of noise facilitate perception in animal models (Atiani et al, 2009), and neural adaptation may also support noise exclusion in humans (Parbery-Clark et al, 2011). Third, neural coding deficits in auditory thalamus and brainstem have been found in dyslexia for tasks that use consistent stimulus or noise features (Chandrasekaran et al, 2009; Díaz et al, 2012). Our observation of dysfunction in cortical adaptation suggests these may be systems-level deficits, given corticofugal signaling is responsible for modulating auditory representations in thalamus and brainstem (Chandrasekaran et al, 2014; Suga et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A number of cross-sectional MRI studies with adults and children have suggested that functional deficits and structural disruptions of the thalamus are a cause of developmental dyslexia (Diaz, Hintz, Kiebel, & von Kriegstein, 2012;Jednoróg et al, 2015;Livingstone, Rosen, Drislane, & Galaburda, 1991;Preston et al, 2010). Skeide et al (2017) recently combined a controlled longitudinal reading intervention with resting-state fMRI in a sample of 30 illiterate Indian adults.…”
Section: Functional Neuroimagingmentioning
confidence: 99%